Answer:
x = 7; y = 3
Explanation:
Set your system of equation. Let one number = x, and the other = y.
x + y = 10
3y - 2 = x
Plug in 3y - 2 for x in the first equation.
(3y - 2) + y = 10
Simplify. Combine like terms.
3y + y - 2 = 10
4y - 2 = 10
Isolate the variable, y. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS. First, add 2 to both sides.
4y - 2 (+2) = 10 (+2)
4y = 10 + 2
4y = 12
Next, divide 4 from both sides.
(4y)/4 = (12)/4
y = 12/4
y = 3
Plug in 3 for y in one of the equations.
x + y = 10
x + 3 = 10
x + 3 (-3) = 10 (-3)
x = 10 - 3
x = 7
x = 7; y = 3
Check:
x + y = 10
(7) + (3) = 10
(10) = 10 (True).
3y - 2 = x
3(3) - 2 = (7)
9 - 2 = 7
7 = 7 (True).
~